Information Seeking Behaviour of Grass Root Level Extension Workers of the Department of Agricultural Extension in Bangladesh - MD JAVED AZAD; Kh Zulfikar Hossain; Hossain Al Mufthi; Md Sekender Ali; Md Masum Abdullah (Journal of Agricultural Extension, 2018)
This study assessed the information searching behaviour of root level extension workers (SAAOs) to explore the relationships between the selected characteristics of the root level extension workers and their information searching behaviour. Chawgacha, Jhikargacha and Jessore Sadar upazila under Jessore district were the study area. All the 70 Sub Assistant Agriculture Officers (SAAOs) in these three upazilas participated in the study. The study revealed that 64.30%of the respondents were frequent information searcher Findings reveal that job satisfaction and aspiration for training had positive significant relationship with information searching behaviour while age, experience of extension work, annual expenditure, and motivation for searching job related information, organizational problem confrontation and technical knowledge had no significant relationship with information searching behaviours.